If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4.9(x + 13) = 8 Reorder the terms: 4.9(13 + x) = 8 (13 * 4.9 + x * 4.9) = 8 (63.7 + 4.9x) = 8 Solving 63.7 + 4.9x = 8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-63.7' to each side of the equation. 63.7 + -63.7 + 4.9x = 8 + -63.7 Combine like terms: 63.7 + -63.7 = 0.0 0.0 + 4.9x = 8 + -63.7 4.9x = 8 + -63.7 Combine like terms: 8 + -63.7 = -55.7 4.9x = -55.7 Divide each side by '4.9'. x = -11.36734694 Simplifying x = -11.36734694
| [5+(-3)]+2=5+[(-3)+2] | | P(p+1)=132 | | P(p+1)=12 | | [7(m+5)-15]+[3(m-2)+2]= | | H=16t^2+75t+4 | | X^5y^4/3xy/1/x^3y | | x+71+x+92=89 | | X^2-9/x-3=5 | | 6sin^2(x)-sin(X)-1=0 | | 5p+7=12+3p | | 186=2x | | X(5x+8)(7x-3)=0 | | -36x=-720 | | -70x=-560 | | 126=x+92 | | 2+6x=2+4x | | 26x=-78 | | -32x=96 | | -3x=108 | | -48x=96 | | -26x=104 | | c^2=-2c+45 | | x^2+2ax+a^2-9=0 | | -x=397 | | 41-7x=160 | | c^2=2c+16 | | 4(3x-1)=6(x-1) | | 23+x=19+11 | | 4x+3.75=x-6 | | Y=7/17 | | 11.3y=4052 | | (2y-5x-4)-(x-6y+5)= |